Serum Ferritin Concentration in Corona Virus Disease 19 - Singh, Samir; Darnal, Sujit Kumar; Chand, Arun Bahadur (Nepal Journal of Health Sciences, 2021)
Introduction: Coronavirus disease 19 (COVID-19) is a complex disease responsible for the development of exacerbated inflammatory response (cytokine storm) that ultimately leads to multiorgan failure and death. Serum ferritin has been recently identified as one of the inflammatory markers responsible for the pro-inflammatory effects. Small amount of ferritin is present in plasma (15-150 ng/mL) which might increase with the severity of COVID-19. Therefore, measurement of ferritin is essential in identifying disease severity and predict disease prognosis. Objective: This study aims to assess the ferritin level in COVID-19 patients. Methods: A cross-sectional study was carried out on 259 COVID-19 patients visiting KIST Medical College and Teaching Hospital (KISTMCTH), Lalitpur, Nepal from November 2020 to April 2021. Serum ferritin was estimated in the automated Siemens ADVIA Centaur CP Chemiluminescence Immunoassay system. All the patients visiting KISTMCTH referred by clinician for ferritin assessment were included in this study. Data collected using the proforma tool was tabulated in SPSS 21 and statistical analysis was done by inferential statistical test. Results: Out of total 259 COVID-19 patients, 58.7% were male and the majority of patients (82.6%) were below 70 years of age. The mean age for all participants was 52.11±16.59 years. Hyperferritinemia was seen in 218 (84.16%) COVID -19 patients. The mean value of serum ferritin was 767.1±789.86 (IQR: 12.8-4590) ng/mL and was significantly higher in males (p<0.001). Comparing the mean values of ferritin between the patients below and above 70 years, no statistical difference was observed (p=0.872). Conclusions: In our study, serum ferritin levels were greatly increased in patients with COVID-19 infection. Keywords: Coronavirus disease 19; cytokine storm; inflammatory marker; serum ferritin.